The «female school teacher’s profile» promoted by educational literature in elizabethan Spain - Rodríguez Álvarez, Marcos; Monarca, Héctor; Mottareale, Daria; Puertas Yáñez, Amaya (Historia y Memoria de la Educación, 2025)
The present work investigates the conception of the female teaching profession at the time of its emergence in Spain, which occurred in the central section of the 19th century, during the reign of Isabel II. For this purpose, we use the analysis of the discourse expressed in the manuals intended for their formation, taking into consideration three main dimensions: considerations of a social nature about the female school teacher, nature of her training and conception within the labor framework. The maternal attributions with which the female magisterial figure was clothed, used to justify the presence of women in a field that until now had been exclusively male, are also attributed to guide the conditions with which their incorporation into it was allowed. The figure of the teacher will be defined in attention to her supposed condition as a woman, dominant essentialist and naturalized, following the canons of the feminine ideal formulated by the bourgeoisie. Thus, impelled to train good future mothers and wives through not only words, but fundamentally example, literature imprisoned the profile of the teacher within the mold of the feminine archetype of self-denial, modesty and submission that they were called to reflect and impart, configuring for them a devalued professional model, both at the training and remunerative level.